Immune-priming of the Tumor Microenvironment by Radiotherapy. (February 2015) - Shahabi, Vafa; Postow, Michael A.; Tuck, David; Wolchok, Jedd D.
<x xml:space="preserve">Abstract</x> A clear contribution of the immune system to eradication of tumors has been supported by recent developments in the field of immunotherapy. Durable clinical responses obtained after treatment with immunomodulatory agents such as ipilimumab (Yervoy) and anti-PD-1 antibody (BMS-936558), have established that harnessing the immune response against chemoresistant tumors can result in their complete eradication. However, only a subset of patients benefit from these therapeutic approaches. Accumulating evidence suggests that tumors with a preexisting active immune microenvironment might have a better response to immunotherapy. In a number of preclinical and clinical studies, many cytotoxic agents elicit changes within tumors and their microenvironment that may make these malignant cells more sensitive to an efficient immune cell attack. Therefore, it is plausible that combining immunotherapy with standard anticancer therapies such as chemotherapy or radiotherapy will provide synergistic antitumor effects. Despite a large collection of preclinical data, the immune mechanisms that might contribute to the efficacy of conventional cytotoxic therapies and their combinations with immunotherapeutic approaches have not yet been extensively studied in the clinical setting and warrant further investigation. This review will focus on current knowledge of the immunomodulatory effects of one such cytotoxic treatment, radiotherapy, and explore different pathways by which its combination with immunomodulatory antibodies might contribute toward more efficacious antitumor immunity.